Temporal Characteristics of Response Integration Evoked by Multiple Whisker Stimulations in the Barrel Cortex of Rats - Shimegi, Satoshi; Ichikawa, Takehiko; Akasaki, Takafumi; Sato, Hiromichi (The Journal of neuroscience, 1999)
We investigated the responses of 114 cells in the barrel cortex of rats to describe the temporal characteristics of excitatory interactions among neurons serving two vibrissae. To examine these interactions, the principal whisker and one adjacent whisker in the same row were stimulated simultaneously or serially at various interstimulus intervals (ISIs). In 37% of the cells tested, combined stimulation of two whiskers exhibited response facilitation; the response to the combined stimulus was larger than the sum of the responses to stimulation of the individual whiskers. The occurrence and magnitude of the facilitation were strongly dependent on the ISI. The ISI capable of producing facilitation for a particular cell was tuned to a narrow range (mean ± SD, 5.3 ± 2.3 msec). The ISI that evoked the maximal facilitation was 1.3 ± 1.3, 3.4 ± 2.3, and 2.8 ± 4.5 msec for neurons in layers II/III, IV, and V/VI, respectively. These ISIs corresponded to the difference in latencies between the responses to the individual stimulations of the principal and adjacent whiskers. A significant response facilitation was observed in the regular-spiking cells but not in the fast-spiking cells. When the ISI was longer than the range that evoked facilitation, a suppression of the response to the second whisker stimulation was observed. Facilitation was observed predominantly in layer II/III cells (69%) and to a lesser extent in cells of layers IV (15%) and V/VI (24%). Our results suggest that, in the barrel cortex, the temporal relationships among tactile stimuli are coded by facilitatory and inhibitory interactions among neurons located in neighboring barrel columns.